2015
DOI: 10.1007/s00345-015-1600-x
|View full text |Cite
|
Sign up to set email alerts
|

Female stress urinary incontinence and the mid-urethral sling: Is obstruction necessary to achieve dryness?

Abstract: As a discipline, we need to conceptualize stress incontinence due to urethral hypermobility or intrinsic sphincter deficiency as separate entities and design our procedures to restore the underlying suspected pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Isovolumetric strength has been shown to improve selection of men considering anti-incontinence surgery [ 28 ]. Given the low pressures at which women void [ 29 ], the application of the Marshall-Marchetti test to simulate outlet resistance at time of urodynamics could represent a future research opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…Isovolumetric strength has been shown to improve selection of men considering anti-incontinence surgery [ 28 ]. Given the low pressures at which women void [ 29 ], the application of the Marshall-Marchetti test to simulate outlet resistance at time of urodynamics could represent a future research opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…SUI has attracted the attention of gynaecologists at home and abroad, and has led to the rise and development of related disciplines such as gynaecology urology and female pelvic floor reconstruction surgery. At present, pelvic sling suspension is recommended as a first‐line treatment of SUI, especially the middle urethral suspension 27,28 . It has been reported that the operation has the advantages of minimally invasive incision, shorter operation time and quicker recovery time after surgery 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Several experts claim that it is paramount to continue to pursue various mechanisms by which to address SUI, so as not to become complacent with the negative factors associated with this procedure. This is propelled by recent data, which illustrates the adverse events associated with MUS [7,8]. Although of relatively low incidence, it is imperative to recognize these complications and understand how to remedy undesirable events potentially resulting from this treatment method.…”
Section: Introductionmentioning
confidence: 89%